Autopsy case of spinocerebellar ataxia type 31 with severe dementia at the terminal stage. Issue 3 (11th December 2014) - Adachi, Tadashi; Kitayama, Michio; Nakano, Toshiya; Adachi, Yoshiki; Kato, Shinsuke; Nakashima, Kenji
<x xml:space="preserve">Abstract</x> Spinocerebellar ataxia type 31 (SCA31) is an autosomal dominant cerebellar ataxia commonly observed in Japan. However, few neuropathological examinations have been conducted. Here we report the case of a 76‐year‐old Japanese male SCA31 patient. He noticed dysarthria and difficulty walking at 65 years old. His symptoms subsequently deteriorated, although he could still walk with assistance at 70 years. At 73 years, when he could no longer walk, he was admitted to our hospital. He showed severe limb and truncal ataxia. His father and older brother had shown the same symptoms. Brain magnetic resonance imaging showed cerebellar atrophy of the anterior lobe and white matter hyperintensities. He was diagnosed with SCA31 by genetic analysis. Gradually, his cognitive functions and ability to communicate declined. He died of respiratory failure at the age of 76. Neuropathological examination revealed severe Purkinje cell loss that was accentuated in the anterior lobe of the cerebellum. Furthermore, the remaining Purkinje cells showed abnormal processes (that is, halo‐like amorphous materials), as has been reported previously. Severe deposition of hyperphosphorylated tau‐positive neurites, many senile plaques and amyloid angiopathy were observed in the neocortex. Our findings suggest that in SCA31, accelerated tau and amyloid pathology in the neocortex might induce dementia at the terminal stage.